HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA TANGAN DENGAN HASIL FREE THROW PADA CLUB BASKET PUTRA CHICKEN SOUP PEKANBARU - Yumnaa Saputri Al’aziz; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted with the aim to find out more about the relationship of wrist flexing and hand eye coordination with the results of the free throw at the Pekanbaru chicken soup men's basketball club. The problem found in this research is that in this basketball club, free throws in every game, there are always free throws that do not enter as a result, points are always wasted. The study was conducted at Gelap Senapelan Pekanbaru, which is located on Jl. Ahmad Yani Pekanbaru. Held in February to May. The population in this study were members of the Pekanbaru chicken soup men's basketball club. While the sampling technique used is sample research, which uses a portion of the population. Based on the results of the study, the following conclusions can be drawn: 'there is a strong relationship between wrist flexing and free throw results, where rtab at a significant level α (0.05) = 0.602 means rcount (0.964)> rtab (0.602), there is a very strong relationship between hand eye coordination and free throw results, where rtab is at a significant level α (0.05) = 0.602 means r count (0.651)> rtab (0.602), there is a very strong relationship together between wrist flexing hand and hand eye coordination with the results of the free throw at the Pekanbaru chicken soup men's basketball club, where rtab at a significant level α (0.05) = 0.602 means r count (0.962)> rtab (0.602).Key Words: Wrist Speculation, Hand Eye Coordination, Free Throw